Outcome of Long-Segment Fixation versus Inclusion of the Fractured Level in Short-Segment Fixation for Thoracolumbar Junction Fractures - El Khateeb, Eslam El Sayed; Tammam, Ahmed G.; Hamdan, Ali R. (Asian Journal of Neurosurgery, 2022)
Objective The aim of this study was to compare the radiological outcomes of long-segment fixation and short-segment fixation, including the fracture level in patients treated for thoracolumbar junction fractures.Methods Data collected from records of patients with thoracolumbar junction fractures who were operated at our department. Neurological evaluation was done using American Spinal Injury Association classification score. Radiological parameters used were the Cobb's angle, vertebral body compression ratio, the anteroposterior spinal canal diameter, and the anterior and the posterior vertebral body heights. Patients were divided into two groups: group A included patients who underwent long-segment fixation and group B included patients who underwent short-segment fixation with inclusion of the fracture level.Results The mean preoperative Cobb angle was 22.51 degrees in group A and 19.37 degrees in group B. Both groups showed improvement in the postoperative Cobb angle as the mean in group A was 14.17 degrees and in group B was 11.77 degrees. The mean preoperative compression ratio in group A was 82.8%, while in group B it was 76%. The postoperative mean in group A was 89.2%, while in group B, it was 84%. The mean preoperative anterior vertebral body height of the fractured vertebra in group A was 16.7 mm, while in group B, it was 15.18 mm. The mean preoperative posterior vertebral body height in group A was 16.33 mm and that of group B was 19.41 mm. The mean postoperative anterior vertebral body height in group A was 17.66 mm and that of group B was 17.10 mm. The mean postoperative posterior vertebral body height in group A was 17.11 mm and that of group B was 20.79 mm.Conclusion Posterior short-segment fixation with additional screws at the fracture level provides similar—if not better—clinical and radiological outcomes to long-segment fixation in the treatment of thoracolumbar junction fractures.
Keywords: thoracolumbar fractures; long-segment fixation; inclusion of the fractured level